The Effectiveness of Micro-credential Programme from the Perspective of Tourism Students - Azmi, Azila; Zubir, Hanani Ahmad; Farook, Ferial; Noorafizi, Hamizah; Wahab, Ahmad Mu’az Abd (Journal of Ecohumanism, 2024)
Tourism micro-credential programmes have gained significant attention in recent years as a means of enhancing the skills and knowledge of students pursuing careers in the tourism industry. However, it is important to evaluate the effectiveness of these programmes from the perspective of tourism students at various universities in Malaysia. These digital proofs of learning serve as evidence of the learner’s achievements, knowledge, and experience, which can be utilised to progress towards a more comprehensive certification or degree that focuses on a specific topic of study within a shorter time. Despite the increasing use of this platform in recent years, there are limited studies discussing its impact on students’ perceptions and its effectiveness in enhancing their engagement with tourism subjects. Thus, this research was conducted to determine the effectiveness of the micro-credential programmes from the perspective of tourism students so that they can be managed more effectively in higher education institutions. To obtain data, the qualitative technique of interpretive phenomenological analysis (IPA) was applied to thoroughly examine the participants’ actual experiences. The participants were selected among the tourism students from various universities in Malaysia that offer tourism and hospitality courses. The interview data were analysed using thematic analysis, which enabled the identification of four themes and fourteen codes. The findings highlighted that the students have positive experiences following micro-credential programmes. Further research should be carried out to ensure micro-credential programmes stay relevant in a constant tourism industry.